Characteristics of biomechanical properties of child’s foot 5-6 years old in the physical rehabilitation process - Kashuba, Vitaliy; Nosova, Natalia (Journal of Education, Health and Sport, 2017)
Actuality. Pre-school age is the most responsible period in the physical development process and in a child’s personality formation. The disorders in the motor function of the foot are the most common among the various pathologies of a child’s lower extremities. Many researchers have found that unfixed disorders with child’s foot can eventually lead to serious changes throughout the organism and cause pathology. The study of the foot support-spring function peculiarities of children 5-6 years old in the physical rehabilitation process is not sufficiently highlighted in the available special literature. Research objective: to study the support-spring properties of a child’s foot 5-6 years old as a development precondition for the technology of the correction of unfixed disorders in children’s support-motional apparatus with physical rehabilitation using. Research results. It was established that the foot length of preschool children was within the age norm, the minimum length was 135.1 mm, and the maximum one was 201.2 mm. The obtained average statistical data of the metatarsal angle α ° and the heel angle β ° in children 5-6 years old indicate the heterogeneity of the group; the range of the metatarsal angle was in the interval from 0.24° tо 21.52° and the range of the heel angle was from 12.46° to 32.38 ° respectively. We have not established statistically significant differences at the level p> 0.05 in all indicators of the foot support-spring functions of children 5-6 years old with posture disorders and with normal posture. Conclusions. There are three main functions which characterize a normal foot: spring, balancing and pushing. The development process of the support-motional apparatus of children 5-6 years old is influenced by various factors and is subjected to some changes, including pathological. The disorders of the foot motor function occupy the first place among the various pathologies of the lower extremities in children of preschool age. It is known that, in the preschool age, the foot is in the stage of intensive development; its formation has not yet been completed, so any adverse actions can lead to the certain functional changes. Prospects for further research are related to the development and implementation of the concept for the correction and prevention of functional disorders in the support-motional apparatus of senior preschool aged children in the physical rehabilitation process.